Observation of mathematics learning results in Al Biruni Class IV students - Cahyanti; Kartika, Amelia; Laily, Husnul (Nashir Al-Kutub Indonesia, 2023)
This study aimed to observe the results of learning mathematics in fourth-grade students at SDI Al Biruni. The observation method was employed to understand the level of students' understanding of mathematics material and the effectiveness of teaching methods used in the school. The study involved 30 grade IV students as observation subjects. Data were analyzed through qualitative analysis to identify trends and patterns in the observations. The results of this study are expected to have provided an overview of the extent to which grade IV students at SDI Al Biruni mastered mathematics and offered insights into possible improvement efforts in the learning process.